A Composer Goes to War: E. J. Moeran and the First World War - Maxwell, Ian (Journal of the Society for Musicology in Ireland, 2019)
The story of Ernest John Moeran’s experiences during the First World War has long been one of sensational speculation, and a narrative has evolved over the years that has significantly informed the reception and assessment of the composer’s music. Since 2007, the author of this paper has examined a mass of evidence, much of it previously unknown or disregarded, which has called into question the reliability of this narrative. Following the 100th anniversaries both of Moeran’s injury at the Second Battle of Bullecourt in northern France on 3 May 1917, and of the ending of the First World War on 11 November 1918, this article has been written to present, in unprecedented detail, an evidence-based account of the composer’s war, from its outbreak in August 1914, to his discharge in January 1919, both chronicling what happened to him, and suggesting how his life and work could be reconsidered in the light of the new narrative. Parts of this article derive from a paper by the same author: The Moeran Myth, previously published in British Music, vol. 32 (2010), 26-48, and from conference papers delivered by the author at ‘Music in Ireland: 1916 and Beyond’, Dublin, April 2016: Moeran in Ireland, 1917-1918 and 1935, and ‘A Great Divide or a Longer Nineteenth Century: Music, Britain and the First World War’, Durham, January 2017: A Composer Goes to War—E. J. Moeran and the First World War.